ANALYSIS AND OPTIMIZATION OF HYDROCYCLONE GEOMETRY USING BOX-BEHNKEN AND MULTI-OBJECTIVE OPTIMIZATION ALGORITHM - MOHD NOR, MOHD AZRI (2021)
Sand presence in oil and gas industry is detrimental to oil extraction operations as it leads to erosion issues and downtime that leads to higher operating cost. Hydrocyclone is considered as promising tool due to its high efficiency, fast processing and small footprint in comparison to gravity settling tank. However, the process of designing an optimal hydrocyclone is difficult due to its sensitivity to many parameters such as geometrical dimensions and operational parameters which is still lacking. The lack of understanding and non-linear modelling of hydrocyclone geometry against performances hamper any optimization process. Therefore, the objectives of this research are to investigate hydrocyclone geometrical parameters impact onto performance (pressure drop, flow split and separation efficiency) using Box-Behnken, analysis of multivariate analysis of variance of geometrical parameters against performances and investigate and validate the effectiveness of multi objective optimization algorithm. The analysis shows all geometrical parameters are significant to pressure drop.